Government Finance Statistics Yearbook 2016. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2017)
This annual publication provides detailed data on transactions in revenue, expense, net acquisition of assets and liabilities, other economic flows, and balances of assets and liabilities of general government and its subsectors. The data are compiled according to the framework of the 2014 Government Finance Statistics Manual, which provides for several summary measures of government fiscal performance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet